The Association Between Prolactin and Metabolic Parameters in PCOS Women: A Retrospective Analysis - Yang, Haiyan; Di, Junbo; Pan, Jiexue; Yu, Rong; Teng, Yili; Cai, Zhuhua; Deng, Xiaohui (Frontiers in Endocrinology, 2020)
Background: The aim of this retrospective study was to analyze the association between prolactin (PRL) and metabolic parameters in infertile patients with polycystic ovary syndrome (PCOS). Methods: A total of 2052 patients with PCOS and 9696 patients with tubal infertility (non-PCOS) undergoing in vitro fertilization and embryo transfer (IVF-ET) at the reproductive medicine center of the first affiliated hospital of Wenzhou Medical University from January 2007 to July 2017 were enrolled in this study. Serum PRL, basic endocrine hormones, fasting plasma lipid, fasting plasma glucose (FPG), liver function, thyroid hormone and other parameters were measured and analyzed. Result: PRL levels were significantly lower in PCOS patients than controls over all age groups (p < 0.05). In the PCOS patients, serum PRL was significantly and positively correlated with FPG, serum TSH and serum FT4, and significantly and negatively correlated with LH, LH/FSH, TC, TG, LDL-C, AST, ALT, Ƴ -GGT, FT3 and FT3/FT4 (p < 0.05 or 0.01). After adjusted for age and body mass index (BMI), serum PRL was positively correlated with FPG, TSH and FT4, and negatively correlated with LH and LH/FSH. Conclusion: Low serum PRL may be an important cause of metabolic risk in infertile patients with PCOS.